Non-Fermi-Liquid Behavior in Metallic Quasicrystals with Local Magnetic Moments - Andrade, Eric C. [UNESP] (2015)
Motivated by the intrinsic non-Fermi-liquid behavior observed in the heavy-fermion quasicrystal Au51Al34Yb15, we study the low-temperature behavior of dilute magnetic impurities placed in metallic quasicrystals. We find that a large fraction of the magnetic moments are not quenched down to very low temperatures T, leading to a power-law distribution of Kondo temperatures P(T-K) similar to T-K(alpha-1), with a nonuniversal exponent alpha, in a remarkable similarity to the Kondo-disorder scenario found in disordered heavy-fermion metals. For alpha < 1, the resulting singular P(T-K) induces non-Fermi-liquid behavior with diverging thermodynamic responses as T -> 0.